All-Trans Retinoic Acid Attenuates Transmissible Gastroenteritis Virus-Induced Inflammation in IPEC-J2 Cells via Suppressing the RLRs/NF‐κB Signaling Pathway - Pu, Junning; Chen, Daiwen; Tian, Gang; He, Jun; Huang, Zhiqing; Zheng, Ping; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Luo, Yuheng; Yan, Hui; Yu, Bing (Frontiers in Immunology, 2022)
Transmissible gastroenteritis virus (TGEV) infection can cause transmissible gastroenteritis (TGE), especially in suckling piglets, resulting in a significant economic loss for the global pig industry. The pathogenesis of TGEV infection is closely related to intestinal inflammation. All-trans retinoic acid (ATRA) has anti-inflammatory activity and immunomodulatory properties, but it is unclear whether ATRA can attenuate the inflammatory response induced by TGEV. This study aimed to investigate the protective effect of ATRA on TGEV-induced inflammatory injury in intestinal porcine epithelial cells (IPEC-J2) and to explore the underlying molecular mechanism. The results showed that TGEV infection triggered inflammatory response and damaged epithelial barrier integrity in IPEC-J2 cells. However, ATRA attenuated TGEV-induced inflammatory response by inhibiting the release of pro-inflammatory cytokines, including IL-1β, IL-6, IL-8 and TNF-α. ATRA also significantly reversed the reduction of ZO-1 and Occludin protein levels induced by TGEV infection and maintained epithelial barrier integrity. Moreover, ATRA treatment significantly prevented the upregulation of IкBα and NF-κB p65 phosphorylation levels and the nuclear translocation of NF-кB p65 induced by TGEV. On the other hand, treatment of TGEV-infected IPEC-J2 cells with the NF-κB inhibitors (BAY11-7082) significantly decreased the levels of inflammatory cytokines. Furthermore, ATRA treatment significantly downregulated the mRNA abundance and protein levels of TLR3, TLR7, RIG-Ⅰ and MDA5, and downregulated their downstream signaling molecules TRIF, TRAF6 and MAVS mRNA expressions in TGEV-infected IPEC-J2 cells. However, the knockdown of RIG-Ⅰ and MDA5 but not TLR3 and TLR7 significantly reduced the NF-κB p65 phosphorylation level and inflammatory cytokines levels in TGEV-infected IPEC-J2 cells. Our results indicated that ATRA attenuated TGEV-induced IPEC-J2 cells damage via suppressing inflammatory response, the mechanism of which is associated with the inhibition of TGEV-mediated activation of the RLRs /NF‐κB signaling pathway.